2021
DOI: 10.1002/lno.11704
|View full text |Cite
|
Sign up to set email alerts
|

The mangrove CO2 pump: Tidally driven pore‐water exchange

Abstract: Atmospheric carbon dioxide (CO2) is fixed by mangrove vegetation and stored in its biomass and sediments. Part of the sediment carbon can be exported to coastal waters via tidally driven pore‐water exchange. Here, we quantify pore water‐derived dissolved CO2 export using in situ, high‐resolution observations of 222Rn and CO2 over a spring‐neap tidal cycle in a mangrove‐fringed estuary (Coffs Creek, Australia). 222Rn‐derived pore‐water exchange rates were 11.5–34.9 cm d−1 (23.0 ± 6.7) over 30 tidal cycles. Pore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 51 publications
0
17
1
Order By: Relevance
“…Porewater acidification following CO 2 production from organic matter degradation can drive metabolic carbonate dissolution, which also produces TA 15 . Drainage of intertidal wetland sediments by tidal pumping (porewater export driven by tidal variations in hydraulic gradients) and bio-irrigation (porewater export driven by benthic organisms) transports DIC- and TA-enriched porewater to surface waters and eventually to the coastal ocean 16 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Porewater acidification following CO 2 production from organic matter degradation can drive metabolic carbonate dissolution, which also produces TA 15 . Drainage of intertidal wetland sediments by tidal pumping (porewater export driven by tidal variations in hydraulic gradients) and bio-irrigation (porewater export driven by benthic organisms) transports DIC- and TA-enriched porewater to surface waters and eventually to the coastal ocean 16 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Spatially, extremely high pCO2 values were observed upstream of the mangrove creek at Sites M11 and M12 (Figure 4 and Table S1). This indicates that the influence of mangrove soils became more pronounced upstream of the mangrove creek (Chen et al, 2021;Maher et al, 2013).…”
Section: Discussionmentioning
confidence: 94%
“…The former is the microbial decomposition of the soil organic matter and porewater export through tidal pumping, whereas the latter includes a primary production by phytoplankton and degradation of DOC. Previous studies have reported that 90-100% of the exported DIC and TA from mangrove forests originate from porewater in a mangrove swamp via tidal pumping (Chen et al, 2021;Maher et al, 2013;Taillardat et al, 2018). The mean value of Chl.…”
Section: Discussionmentioning
confidence: 98%
“…Groundwater in mangroves is a mixture of seawater infiltration and inland freshwater (Chen et al., 2021). Both terrestrial plant litter and soil are important sources of DOM to groundwater (McDonough et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Groundwater flow in mangroves plays an important role in enhancing above‐ground growth (Hayes et al., 2019) and is often driven by tidal flows (Tait et al., 2016). The concept of “tidal pumping” highlights the significance of water exchange on soluble outwelling from mangroves to nearby coastal waters (Chen et al., 2021; Santos et al., 2021; Zheng et al., 2016). Tidal pumping requires that surface water infiltrates into the sediments during flood tides, and that groundwater mixed with surface water eventually discharges when sea level is lower.…”
Section: Introductionmentioning
confidence: 99%